2003
DOI: 10.1007/s11615-003-0096-y
|View full text |Cite
|
Sign up to set email alerts
|

Die Umsetzung von EU-Richtlinien im Zeichen der Parteipolitik: Eine akteurszentrierte Antwort auf die Misfit-These

Abstract: Vor dem Hintergrund der Debatte über die Steuerungsfähigkeit der EU befasst sich dieser Beitrag mit der Frage, welche Faktoren zu einer korrekten und pünktlichen Umsetzung von EU-Richtlinien beitragen. Er setzt sich mit der häufig vertretenen Misfit-These auseinander, der gemäß Qualität und Schnelligkeit der nationalen Anpassung vor allem durch das Ausmaß der Kompatibilität zwischen europäischen Vorgaben und bestehenden nationalen Strukturen bestimmt wird. Anhand empirischer Ergebnisse über die Umsetzung von s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 19 publications
0
33
1
4
Order By: Relevance
“…Along these lines, Treib (2003aTreib ( ,b, 2004 showed that party political preferences of governments may have a decisive impact on transposition outcomes. In particular, he takes issue with the behavioural assumptions underlying the mainstream misfit argument, notably that domestic governments will always try to defend their existing policy traditions.…”
Section: The Third Wave: Theoretical and Methodological Differentiationmentioning
confidence: 99%
“…Along these lines, Treib (2003aTreib ( ,b, 2004 showed that party political preferences of governments may have a decisive impact on transposition outcomes. In particular, he takes issue with the behavioural assumptions underlying the mainstream misfit argument, notably that domestic governments will always try to defend their existing policy traditions.…”
Section: The Third Wave: Theoretical and Methodological Differentiationmentioning
confidence: 99%
“…This misfit argument involves an institutional, legal, normative, and policy misfit -the latter having been investigated most frequently. Whereas some studies find robust evidence for this argument, others demonstrate little or no support and reveal the limited explanatory power of the misfit thesis (Treib 2003, Mastenbroek 2005Haverland 2000;Falkner et al 2005;Mastenbroek/Kaeding 2006). In line with this misfit argument, member states that were unable to advocate ('upload') their preferences at EU level might evade implementation or compliance in order to oppose the introduction ('downloading') of EU policies at the national level or in order to protect their national structures and administrations (Falkner et al 2004, 453;Knill/Lenschow 2000, 261-262).…”
Section: Europeanisation and Implementationmentioning
confidence: 99%
“…From the literature, we know that implementation problems due to structural misfits between policy levels are only a part of the explanation for implementation difficulties; other reasons for implementation difficulties can be found in the belief systems and preferences of actors, in particular policy preferences and choice of policy instruments of actors on the respective levels, which effect transposition, interpretation, application and enforcement [18,19]. This finding regarding the role of actors and their ideas is very important for our topic.…”
Section: The Goals Of Sustainable Development and Sustainability Polimentioning
confidence: 99%